2015
DOI: 10.5296/ijhrs.v5i3.8376
|View full text |Cite
|
Sign up to set email alerts
|

Linkage between Perceived Corporate Social Responsibility and Employee Engagement: Mediation Effect of Organizational Identification

Abstract: This study employs structural equation modelling technique to examine the direct effect of perceived external corporate social responsibility and perceived internal corporate social responsibility on employee engagement as well as the mediated link through organizational identification. Social exchange theory and social identity theory used to explain the relationships between the variables in this study. It was conducted among 1080 employees of four selected organizations in Iran which are among the main pion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
1
9
1
Order By: Relevance
“…Opoku‐Dakwa, Chen, and Rupp () suggested that organizational support for CSR initiatives are more conducive to employee engagement and job meaningfulness. Literature shows that there is a significant positive relationship between CSR perception and employee's work engagement (Esmaeelinezhad, Singaravelloo, & Boerhannoeddin, ; Glavas, ; Opoku‐Dakwa, Chen, & Rupp, ). Accordingly, we hypothesize the following:Hypothesis CSR perception positively affects employee engagement.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Opoku‐Dakwa, Chen, and Rupp () suggested that organizational support for CSR initiatives are more conducive to employee engagement and job meaningfulness. Literature shows that there is a significant positive relationship between CSR perception and employee's work engagement (Esmaeelinezhad, Singaravelloo, & Boerhannoeddin, ; Glavas, ; Opoku‐Dakwa, Chen, & Rupp, ). Accordingly, we hypothesize the following:Hypothesis CSR perception positively affects employee engagement.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In contrast, Singh, Sethuraman, and Lam (2017) found that they are significantly related to each other. Esmaeelinezhad, Singaravelloo, and Boerhannoeddin (2015) revealed that ICSR practices are not significantly related to job satisfaction and employee engagement; however, the study of Farid et al (2019) indicated that those variables are actually significantly related. The inconsistency of past studies suggests that more research is needed and that various factors may influence the inconsistencies, such as the environmental and cultural setting of a given nation.…”
Section: Introductionmentioning
confidence: 86%
“…As an exception, Gao, Zhang [15] showed a significant and positive association between CSR perception and employees’ work engagement. Similarly, another study showed a significant association between CSR perceptions and employees’ work engagement mediated by an organizational identification mechanism [55]. Glavas [17] conducted a study of 15,184 employees who were working in a large professional service in USA, and found that CSR has a positive and significant influence on employee work engagement.…”
Section: Theory and Hypothesesmentioning
confidence: 99%